2015
DOI: 10.1158/1541-7786.mcr-14-0389
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase hSETD1A Is a Novel Regulator of Metastasis in Breast Cancer

Abstract: Epigenetic alteration is a hallmark of all cancers. Such alterations lead to modulation of fundamental cancer-related functions, such as proliferation, migration, and invasion. In particular, methylation of Histone H3 Lysine 4 (H3K4), a histone mark generally associated with transcriptional activation, is altered during progression of several human cancers. While the depletion of H3K4 demethylases promotes breast cancer metastasis, the effect of H3K4 methyltransferases on metastasis is not clear. Nevertheless,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 63 publications
(94 reference statements)
1
65
0
Order By: Relevance
“…Knocking down SETD1A reduced the cell growth and metastatic properties of colorectal cancer cells, and had a major impact on attenuating the expression of Wnt/β-catenin genes (Salz et al, 2014b). Reducing SETD1A expression also lowered the metastatic properties of triple negative breast cancer cells, MDA-MB-231 and BT549, and attenuated the expression of matrix metalloproteinases (Salz et al, 2014a).…”
Section: H3k4me3 Writersmentioning
confidence: 98%
See 1 more Smart Citation
“…Knocking down SETD1A reduced the cell growth and metastatic properties of colorectal cancer cells, and had a major impact on attenuating the expression of Wnt/β-catenin genes (Salz et al, 2014b). Reducing SETD1A expression also lowered the metastatic properties of triple negative breast cancer cells, MDA-MB-231 and BT549, and attenuated the expression of matrix metalloproteinases (Salz et al, 2014a).…”
Section: H3k4me3 Writersmentioning
confidence: 98%
“…and 1B contribute to the genesis of H3K4me3 (Salz et al, 2014a). Knocking down SETD1A reduced the cell growth and metastatic properties of colorectal cancer cells, and had a major impact on attenuating the expression of Wnt/β-catenin genes (Salz et al, 2014b).…”
Section: H3k4me3 Writersmentioning
confidence: 99%
“…Histone lysine methyltransferases (SETD1 and 2) are found as novel tumor suppressors. Downregulation of SETD2 promotes both initiation and progression in leukemia (Zhu et al 2014), whereas hSETD1A controls tumor metastasis by activating MMP expression (Salz et al 2014). An upregulation of EZH2 (Enhancer of Zeste 2, a histone methyltransferase) has been observed in a wide variety of tumors, such as prostate cancer, lymphomas, colorectal and gastric cancer, and bladder and breast cancer.…”
Section: Epigenetic Modifications In Cancermentioning
confidence: 99%
“…19 Additionally, the regulation of multiple matrix metalloproteinase (MMP) genes by SETD1A has been identified as a major mechanism for promoting metastasis of MDA-MB-231 cells. 20 Our recent studies revealed that SETD1A also plays an important role in estrogen-mediated gene expression. 21,22 However, the clinical significance of SETD1A in ER-positive breast cancer, which accounts for over 70% of all breast cancers, is not clear.…”
Section: Introductionmentioning
confidence: 99%